2021
DOI: 10.1093/genetics/iyab231
|View full text |Cite
|
Sign up to set email alerts
|

A tandem duplication in Drosophila melanogaster shows enhanced expression beyond the gene copy number

Abstract: Tandem duplicated genes are common features of genomes, but the phenotypic consequences of their origins are not well understood. It is not known whether a simple doubling of gene expression should be expected, or else some other expression outcome. This study describes an experimental framework using engineered deletions to assess any contribution of locally-acting cis- and globally-acting trans-regulatory factors to expression interactions of particular tandem duplicated genes. Acsx1L (CG6300) and Acsx1R (CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Although a simple prediction holds that duplicating a gene will double the gene expression level, current studies suggest that deviations from this two-fold hypothesis are frequent for transgenic and naturally occurring tandem duplicates (Cardoso-Moreira et al 2016;Lan and Pritchard 2016;Loehlin and Carroll 2016;Hayward et al 2017;Rogers et al 2017;Konrad et al 2018;Loehlin et al 2022).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Although a simple prediction holds that duplicating a gene will double the gene expression level, current studies suggest that deviations from this two-fold hypothesis are frequent for transgenic and naturally occurring tandem duplicates (Cardoso-Moreira et al 2016;Lan and Pritchard 2016;Loehlin and Carroll 2016;Hayward et al 2017;Rogers et al 2017;Konrad et al 2018;Loehlin et al 2022).…”
Section: Introductionmentioning
confidence: 84%
“…Three of four tandem duplications produced about twice the activity of the single-copy lines, while the fourth, TD10/5.16, showed lower expression. The observed variation among tandem duplicate lines is intriguing, in light of the results of past studies that observed deviations from two-fold expression (Loehlin and Carroll 2016;Hayward et al 2017;Rogers et al 2017;Konrad et al 2018;Loehlin et al 2022). Several mechanisms have been hypothesized that could explain why a tandem duplicated gene expresses differently from the sum of two singletons (Loehlin et al 2022).…”
Section: Expression Of Tandem Duplicates From Varying Starting Positionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is likely that selection favors genetic and cellular mechanisms that facilitate abundant gene expression, and increased MaSp copy numbers may be one pathway for achieving this goal. It is noteworthy that all of the recent MaSp paralogs in Argiope are organized in a tandem configuration because two recent studies [ 82 , 83 ] have found that tandem orientation boosts gene expression levels beyond the expected two-fold increase. However, why selection for increased gene expression might be greater in Argiope than other spiders is unclear.…”
Section: Discussionmentioning
confidence: 99%